Prazgodovinska kamnita in koščena tolkala, drgala, samozveneči idiofoni, ropotulje in brnivke - Omerzel-Terlep, Mira (Etnolog. Nova vrsta (Ljubljana), 1998)
Prehistoric percussion instruments, scrapers, rattles, idiophones and bullroarers made of stone, bone, clay, and metal are instruments which deserve to be studied in greater detail by musicology and by as yet young science of archaological ethnomusicology in the future. The author intoduces us to the research that has been carried out on these instruments and provides comparison with relevant archaological finds from the Slovene territory.
Keywords: inštrumenti; prazgodovina; Slovenia; Slovenija; ethnology; etnologija; muzikologija; arheološke najdbe